2004
DOI: 10.1063/1.1829167
|View full text |Cite
|
Sign up to set email alerts
|

Free-standing, optically pumped, GaN∕InGaN microdisk lasers fabricated by photoelectrochemical etching

Abstract: GaN-based, mushroom-shaped microdisk lasers were fabricated using band-gap selective photoelectrochemical etching. The optically pumped microdisks had well-defined, distinct modes at excitation powers ranging from about 8to16W∕cm2. Modal linewidths of 0.09nm were reported, which was near the resolution of the measurement equipment. Quality factors for the microdisks were >4600. The observed lasing threshold was 12.1W∕cm2. At higher excitation powers, heating effects and degradation were observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 23 publications
2
60
0
Order By: Relevance
“…7,8 However, the superior optical confinement capabilities of GaN WGM microcavities are invariably weakened by optical leakage through its transparent sapphire substrate. Recently, GaN-based undercut two-dimensional (2D) WGM microdisk lasers fabricated through the removal of sacrificial layers embedded within the device structure by photoelectrochemical (PEC) or selective wet-etching [9][10][11] have been reported to effectively reduce such losses. Similar undercut microdisk structures have also been demonstrated by controlled wet-etch removal of the underlying Si substrate using GaN-on-Si materials.…”
mentioning
confidence: 99%
“…7,8 However, the superior optical confinement capabilities of GaN WGM microcavities are invariably weakened by optical leakage through its transparent sapphire substrate. Recently, GaN-based undercut two-dimensional (2D) WGM microdisk lasers fabricated through the removal of sacrificial layers embedded within the device structure by photoelectrochemical (PEC) or selective wet-etching [9][10][11] have been reported to effectively reduce such losses. Similar undercut microdisk structures have also been demonstrated by controlled wet-etch removal of the underlying Si substrate using GaN-on-Si materials.…”
mentioning
confidence: 99%
“…However, due to the optical diffraction limit of the light source, the photolithography process can hardly reproduce the mask pattern with accuracy at sub-wavelength scales. More importantly, erosion of the photoresist structures during dry-etching induces imperfections to the circularity and sidewall roughness of the fabricated microdisks [28], as shown in Fig. 6a and b.…”
Section: Feature Articlementioning
confidence: 99%
“…This process was developed by Haberer et al [7] and further refined by Tamboli et al [4], who suggested that due to the polarisation inherent within c-plane nitrides, the sacrificial layer should consist of a super-lattice in order to modulate the band edge and ensure a homogenous distribution of photogenerated holes across the layer surface during the etch process. The growth of such heterostructures is in itself a challenge, due to the accumulated strain between the heterostructure layers, and potential strain relaxation, which can generate extra dislocations (in addition to those already present in the pseudo-substrate).…”
Section: Introductionmentioning
confidence: 99%